IDENTIFICATION OF DIFFERENCES IN VIRULENCEFACTORS PRODUCTION FROM UV IRRADIATED ISOLATEOF CLINICAL Vibrio cholerae S - Al- Khafaji, K.; Al- Thwani, A. (Iraqi Journal of Science, 2024)
Mutants from the clinical isolate of Vibrio cholerae S were isolated after UVirradiation on the basis of antibiotic resistance for Rifampcin, Streptomycin andKlindamycin. Results revealed that the highest antibiotic resistant incidence is forRifampicin after UV exposure for 15 minute.One thousand mutant isolates were examined and showed smaller sized colonies onTSA appeared as smooth and translucence with yellow color on TCBS agar and paleon MacConkey agar. The mutant isolates gave positive results with oxidase andstring test. Autoagglutination range from high level order designated +++ to mild ++and low level designated as +. Only 15% of Rifampicin resistant mutant isolatesgave no agglutination phenomenon. UV treated isolates produced delayed type ofproteases with no changes in haemolycin and lipases production while, slightlyautoagglutination has been detected from these mutant. Twenty out of screenedisolates produced 10-30U/ml of CT at non- permissive conditions.The toxin extract from mutant isolates symptoms such as muscle spasm, musclecramp, exhaustion, trummer and tachycardia in mice after intraperitoneal injection.Erythemal effect and induration in the injected site of Guinea pig skin afterintradermal injection remained even after more than one week, with pronouncedbleeding detected in the injected area.